An optimal construction of smart aged homes based on SDLC using smart sensors and agent networks - R. Subha; Jun Zhang (International Journal of Intelligent Networks, 2022)
With the increased growth of the added population group and advancements in health informatics, the smart aged home needs to be equipped with intelligent systems and various electronic devices. Industry 5.0 is yet another revolution that bought about the transformation in the practices concerning the use of intelligent technology with smart sensors and agent networks. Smart sensors enabled industry 5.0 is equipped with automation and self-monitoring ability that assists with analyzing the issues without the intervention of human beings. We, in this paper, proposed an iterative development process based on the smart sensor and agent networks of the SDLC software development models. The proposed model is developed by synchronizing the smart aged home with the cyber-physical system of industry 5.0. The quality value matrix is introduced as a tool to identify the requirements of the residents and the stakeholders. The feasibility of the proposed work is assessed with the help of an agent-based simulation system.